2003
DOI: 10.1007/s00442-003-1196-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in habitat complexity negatively affect diverse gastropod assemblages in coralline algal turf

Abstract: The physical structure of a habitat generally has a strong influence on the diversity and abundance of associated organisms. I investigated the role of coralline algal turf structure in determining spatial variation of gastropod assemblages at different tidal heights of a rocky shore near Sydney, Australia. The structural characteristics of algal turf tested were frond density (or structural complexity) and frond length (the vertical scale over which structural complexity was measured). This definition of stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 55 publications
5
108
1
7
Order By: Relevance
“…If increased CO 2 levels weaken the skeletal structure of C. oYcinalis, the potential combination of increased grazing pressure, slower growth, higher UV stress, and less recruitment will likely cause a phase shift in C. oYcinalis communities toward more Xeshy, non-calcifying macroalgae, and could even amplify changes in competition between non-calcifying algae. While both calcifying and non-calcifying algae provide important habitat and shelter for many marine organisms, erect calcifying algae such as C. oYcinalis contribute to the strength of the intertidal community structure and provide refugia for organisms in environments with high wave action (Stewart 1982;Coull and Wells 1983;Kelaher 2002Kelaher , 2003-all important ecological roles that could be interrupted under high CO 2 conditions.…”
Section: ¡mentioning
confidence: 99%
See 1 more Smart Citation
“…If increased CO 2 levels weaken the skeletal structure of C. oYcinalis, the potential combination of increased grazing pressure, slower growth, higher UV stress, and less recruitment will likely cause a phase shift in C. oYcinalis communities toward more Xeshy, non-calcifying macroalgae, and could even amplify changes in competition between non-calcifying algae. While both calcifying and non-calcifying algae provide important habitat and shelter for many marine organisms, erect calcifying algae such as C. oYcinalis contribute to the strength of the intertidal community structure and provide refugia for organisms in environments with high wave action (Stewart 1982;Coull and Wells 1983;Kelaher 2002Kelaher , 2003-all important ecological roles that could be interrupted under high CO 2 conditions.…”
Section: ¡mentioning
confidence: 99%
“…Corallina spp. often form extensive macroalgal turfs that cover large areas of the intertidal and provides substratum, habitat, and refugia for a number of important marine organisms (Coull and Wells 1983;Hicks 1986;Akioka et al 1999;Kelaher 2002Kelaher , 2003. On the rocky coast of the island of Helgoland in the North Sea, C. oYcinalis is abundant and is an important species in the macroalgal community.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Sanchez-Moyano et al (2001) reported that variation in the associated fauna was related to the life cycle of Caulerpa prolifera. In within-species comparisons, the greatest differences in the species richness and composition of the associated fauna have been associated with size-related characteristics of macroalgae (Russo, 1990;Attrill et al;, Kelaher, 2003a.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively complex architecture of their reefs and beds influences other species to the same extent as their direct effects (Jones et al 1994). Variation in habitat structure (either of biogenic or abiotic nature) generates abundance and diversity patterns in numerous systems studied (see Beck 2000, Kelaher 2003, Hewitt et al 2005, and references therein) affecting recruitment and survival of benthic organisms. McCoy & Bell (1991) suggested quantifying habitat structure in terms of 'habitat complexity' and 'habitat heterogeneity'.…”
Section: Introductionmentioning
confidence: 99%
“…These factors stand for the absolute abundance of structural components and the relative abundance of different compo-nents at a certain spatial scale, respectively. With rare exceptions (Kelaher 2003), increased habitat complexity leads to an increase in diversity of the associated assemblages, which is generally believed to result from expansion of range of possible niches (MacArthur & MacArthur 1961).…”
Section: Introductionmentioning
confidence: 99%